Going Mobile: Aesthetic Design Considerations from Calder and the Constructivists - Barry, David; Rerup, Claus (Organization Science, 2006)
Design thinking has long tried to join form, function, and aesthetic appeal. In cars, furniture, architecture, typography, clothes, or photography, good designs regularly solve problems of movement, massing, and balance in attractive and inspiring ways. The field of organization design is comparatively young in this regard, having mostly focused on questions of efficiency and expediency rather than aesthetics; nevertheless, designers are increasingly being called on to create organizations that “sing” rather than just “work.” Here, we consider how aesthetically sophisticated design thinking from the arts might be applied in organizational design. Specifically, we consider the case of Learning Lab Denmark—a research institute that has experimented extensively with aesthetically informed organizational design—in light of the mobile art of Alexander Calder and other constructivist artists who championed flexible design. We conclude that in such organizations, (1) designers must strike an ongoing, interactive balance between centric and acentric design orientations and practices, (2) aesthetic consideration is fundamentally important when it comes to crafting effective design, and (3) designing processes should be given as much attention as design solutions.